Physiological and Haemato-Biochemical Alterations in the Ketamine-Propofol-Isoflurane and Tiletamine-Zolazepam Isoflurane Anaesthetic Protocols in Cats - Badi, Raisudin N; Vadalia, Jignesh J; Sharma, Anil; Sharma, Arun K; Dodia, Vaibhav D (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present clinical study involved 12 cats of different age, sex, and breed presented for various surgeries, which were randomly divided into two groups, each group consisting of six cats. Induction of anaesthesia was achieved by administration of ketamine @ 2 mg/kg b.wt. in combination with propofol @ 2 mg/kg b.wt., intravenously in group I and tiletamine @ 5 mg/kg b.wt. in combination with zolazepam @ 5 mg/kg b.wt., intramuscularly in group II. It was maintained by isoflurane with 100% oxygen using a face mask connected with small animal inhalant anaesthesia machine. Significant decrease in rectal temperature, respiration rate and plasma total protein, and non-significant alteration in heart rate, SpO2, ALT, BUN and creatinine were observed during the maintenance phase in both groups, but within normal physiological range. However, no significant difference was noted between groups at any point of time in any of the parameters evaluated. Overall satisfactory outcome from the anaesthesia was achieved in both groups, yet group I showed slightly better result than group II.